2014
DOI: 10.1371/journal.pone.0112231
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Air Temperature Changes in the Tarim Basin over 1960–2012

Abstract: There has been evidence of warming rate varying largely over space and between seasons. However, little has been done to evaluate the spatial and temporal variability of air temperature in the Tarim Basin, northwest China. In this study, we collected daily air temperature from 19 meteorological stations for the period of 1960–2012, and analyzed annual mean temperature (AMT), the annual minimum (Tmin) and maximum temperature (Tmax), and mean temperatures of all twelve months and four seasons and their anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The Mann-Kendall analysis presented in this study found a positive trend in temperatures between 1960 and 2016, and the linear regression analysis shows that this change is concentrated in the post-1986 period; and focused in the spring, summer and autumn months. These observations validate previous climatological studies that have found the southern Xinjiang climate to be shifting to a warmer state (Chen and others, 2006; Shi and others, 2007; Peng and others, 2014). Thus, the fact that climate changes are predominantly present in the form of warmer temperatures, rather than increased precipitation, support the hypotheses of Hewitt (2007), relating to long-term warming, over Copland and others (2011), relating to increases in mass balance.…”
Section: Discussionsupporting
confidence: 90%
“…The Mann-Kendall analysis presented in this study found a positive trend in temperatures between 1960 and 2016, and the linear regression analysis shows that this change is concentrated in the post-1986 period; and focused in the spring, summer and autumn months. These observations validate previous climatological studies that have found the southern Xinjiang climate to be shifting to a warmer state (Chen and others, 2006; Shi and others, 2007; Peng and others, 2014). Thus, the fact that climate changes are predominantly present in the form of warmer temperatures, rather than increased precipitation, support the hypotheses of Hewitt (2007), relating to long-term warming, over Copland and others (2011), relating to increases in mass balance.…”
Section: Discussionsupporting
confidence: 90%
“…Temperature increases is one of the most important heat-related issues in climate change research 22 35 36 . Studies have shown that the temperature rise is an objective fact in the entire Tarim Basin 20 37 . The main causes of the temperature rise have generally been attributed to atmospheric circulations, such as the El Niño-Southern Oscillation 20 , the Siberian High 22 , the North Atlantic Oscillation or the Arctic Oscillation 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the temperature rise is an objective fact in the entire Tarim Basin 20 37 . The main causes of the temperature rise have generally been attributed to atmospheric circulations, such as the El Niño-Southern Oscillation 20 , the Siberian High 22 , the North Atlantic Oscillation or the Arctic Oscillation 23 24 . However, the impacts of the oasis effect on temperature have long been ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations